2021
DOI: 10.1002/er.6515
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a nanofluid‐based photovoltaic thermal system usingsingle‐wallcarbon nanotubes: An experimental study

Abstract: Summary The temperature of photovoltaic cell is reduced by heat transfer fluids (HTF) in cooling channels, which are attached to the back of the photovoltaic module in a hybrid thermal photovoltaic system (PV/T). Recently, nanofluids have been implemented as HTF's in PV/T systems. Various types of nanofluids have been synthesized, prepared, and tested, however, not a specific type in particular. In this paper, experiments were carried out using Single‐walled carbon nanotubes (SWCNTs) nanofluids. The proposed n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 69 publications
1
10
0
Order By: Relevance
“…However, it does give some indication of the validity and accuracy of the results of the current study. For example, the results of 93 that used a nanofluid containing MWCNT were higher than the results of 48 study that used a nanofluid containing SWCNT, due to the difference in the type of heat exchanger employed, the coolant mass flow rate and the measurement conditions. The current study produced a high total efficiency that is close to the results of.…”
Section: Referencesmentioning
confidence: 74%
“…However, it does give some indication of the validity and accuracy of the results of the current study. For example, the results of 93 that used a nanofluid containing MWCNT were higher than the results of 48 study that used a nanofluid containing SWCNT, due to the difference in the type of heat exchanger employed, the coolant mass flow rate and the measurement conditions. The current study produced a high total efficiency that is close to the results of.…”
Section: Referencesmentioning
confidence: 74%
“…Al-Waeli et al observed that both EG and PG can act as a lubricant for nanoparticles, thus allowing them to become redistributed if they settle and collect at the bottom of the tank when the liquid is recirculated. Generally, it can be advantageous to combine the trait with the higher thermal conductivity of water by mixing it with the liquids mentioned, such as refs , , , which has led to many investigations.…”
Section: Resultsmentioning
confidence: 99%
“…Nanofluids are a mixture of small-sized solid particles of less than 100 nm with base fluids (water, kerosene, oil, etc.) to produce a nanofluid with better heat transfer properties than the base fluid [2]. Recently, the use of nanofluids has occupied a wide range in heat transfer applications.…”
Section: Introductionmentioning
confidence: 99%